If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 38 + -3x = 4x + -18 Reorder the terms: 38 + -3x = -18 + 4x Solving 38 + -3x = -18 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 38 + -3x + -4x = -18 + 4x + -4x Combine like terms: -3x + -4x = -7x 38 + -7x = -18 + 4x + -4x Combine like terms: 4x + -4x = 0 38 + -7x = -18 + 0 38 + -7x = -18 Add '-38' to each side of the equation. 38 + -38 + -7x = -18 + -38 Combine like terms: 38 + -38 = 0 0 + -7x = -18 + -38 -7x = -18 + -38 Combine like terms: -18 + -38 = -56 -7x = -56 Divide each side by '-7'. x = 8 Simplifying x = 8
| Z-9=54.9 | | h=t^2+5t+6 | | 3x+8-12=2(2x-3)+x | | 1/2(3x2) | | 2/3x9/16 | | 7-5m=18+2m | | (5x-10)=37 | | 5(4+2x)+(-8x+-12)=68 | | (x+24)=(2x-1) | | 5x+24+9x-17=180 | | V+88=88 | | 2(3)+y=-3 | | 192x^2=108 | | 2(9-3z)-3(2z+9)=z-13 | | (5x-10)=360 | | 2(2)+y=-3 | | Y-20=10(x-9) | | 5x(6)=10x+40 | | 7*9=9*7 | | 2(3-2z)-3(2z+7)=z-21 | | 8(x+8)+6=10x-2(x-5) | | 5(x+2)=3X-(x-4) | | -3(2m-4)=21 | | 6x/7x-49 | | -1/4(12x-16)= | | b^2-14b=-48 | | b^2-14b=48 | | -384=-16m | | 6x-6=6x+54 | | 2=3+x^2 | | -6-2t=-1t-1 | | -4/7÷3/14 |